Evaluasi Kelayakan Finansial Usaha Kerupuk Rambak Di Kecamatan Rambah Hilir Kabupaten Rokan Hulu - Yahya, Zakaria; Gunawan, Ikhsan; Away, Sischa Febriani Yamesa (SUNGKAI, 2023)
Evaluation of business feasibility is needed to get an idea of ​​whether it is feasible or not, in running a rambak cracker business, almost all business actors do not apply bookkeeping in their business finances, so they do not know how much the expenses and income are in their business. This research was conducted with the aim of knowing the production techniques, income, and financial feasibility of the rambak crackers processing business. This research was carried out from August 2022 to February 2022. The sampling technique was a saturated sample in the form of a rambak cracker processing business in Hilir District. The current data collection method used was direct interviews and observations at the place of business. The results showed that the rambak cracker production techniques included tool preparation, seasoning refining, mixing, molding, boiling, cutting, drying to packaging, the rambak cracker processing business was declared feasible with a Net Present Value of 126.301.605 which is positive (NPV> 0) Internal The Rate OF Return (IRR) is 56,00% where the IRR value is greater than the applicable discount rate, which is 8.30%, Net B/C is 2,9503 where (Net B/C> 1), Payback Period (PP) is 1 Year 5 Months 27 Days, and Break Even Point (BEP) 3 Year 8 Months 9 Days. All results analyzed with investment criteria stated that the rambak cracker business in Rambah Hilir District was feasible to run.